2016
DOI: 10.1177/1756829316638204
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study on the flow characteristics of micro air vehicle wings at low Reynolds numbers

Abstract: The aerodynamic characteristics around a micro air vehicle wing with an inverse-Zimmerman configuration are numerically investigated by an in-house programmed solver particularly dedicated for aircrafts operating in low Reynolds number regime. The complex three-dimensional aerodynamic performance was investigated in terms of force generation and flow structures visualization. Results show that the flow around the low aspect ratio MAV wing is characterized by complex three-dimensional separation-dominated flow.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The results showed that the thin cambered-plate airfoil generated the highest lifting force compared with the NACA0012. Xiao [ 15 ] studied the aerodynamic performance of Eppler61, Pfenninger048, a thin cambered-plate airfoil and a flat-plate airfoil. The results showed that the thin cambered-plate airfoil provided the highest lift and lift-to-drag (L/D) ratio.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the thin cambered-plate airfoil generated the highest lifting force compared with the NACA0012. Xiao [ 15 ] studied the aerodynamic performance of Eppler61, Pfenninger048, a thin cambered-plate airfoil and a flat-plate airfoil. The results showed that the thin cambered-plate airfoil provided the highest lift and lift-to-drag (L/D) ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, a conventional aircraft modeling techniques that do not take into account of propeller wake are inadequate to model the aerodynamic forces acting on MAV. The aerodynamic effects of propeller flow on MAV and small UAV are studied in [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. The influence of propeller wake on the lift, drag and wing stall characteristics is reported in [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%